Assessment of rabbit spermatozoa characteristics after amygdalin and apricot seeds exposure in vivo. (2018) - Kolesar, Eduard; Tvrda, Eva; Halenar, Marek; Schneidgenova, Monika; Chrastinova, Lubica; Ondruska, Lubomir; Jurcik, Rastislav; Kovacik, Anton; Kovacikova, Eva; Massanyi, Peter; Kolesarova, Adriana
Highlights: Rabbit spermatozoa parameters after amygdalin and apricot seeds exposure. Evaluation of spermatozoa motility by the CASA system. Decrease of spermatozoa motility after intramuscular AMG application. Oral consumption of apricot seeds had no effect on the spermatozoa motility. Our data suggest the potential impact of AMG and apricot seeds on male reproduction. Abstract: This study evaluates rabbit spermatozoa motility parameters after in vivo administration of amygdalin and apricot seeds during a 28-day period. Apricot seeds are potentially useful in human nutrition and amygdalin is the major cyanogenic glycoside present therein. The rabbits were randomly divided into the five groups (Ctrl-Control, P1, P2, P3, P4) with 4 males in each group. Control group received no amygdalin/apricot seeds while the experimental groups P1 and P2 received a daily intramuscular injection of amygdalin at a dose 0.6 and 3.0 mg/kg b.w. respectively during 28 days. P3 and P4 received a daily dose 60 and 300 mg/kg b.w. of crushed apricot seeds mixed with feed during 28 days, respectively. CASA system was used to evaluate for motility, progressive motility, curvilinear velocity, amplitude of lateral head displacement and beat cross frequency. Intramuscular application of amygdalin resulted in a significant time- and dose-dependent decrease of spermatozoa motility as well as progressive motility. On the other hand, oral consumption of apricot seeds had no significant effect either on the rabbit spermatozoa motility or progressive motility over the entire course of the study. The analysis of the other motion characteristics revealed a similar trend depicting a continuous, time- and dose-dependent decrease of all parameters following intramuscular AMG administration, with significant differences particularly for the dose 3.0 mg AMG/kg b.w. On the other hand, oral administration of apricot seeds had no significant impact on spermatozoa motility parameters. The present study suggests that short-term intramuscular application of amygdalin decreased rabbit spermatozoa motility in vivo . Whereas, consumption of apricot seeds did not induce any change in rabbit spermatozoa in vivo . Our findings suggest dose-dependent negative effect of pure amygdalin, but not apricot seeds on the rabbit spermatozoa parameters.